Down-regulation of miR-10a-5p promotes proliferation and restricts apoptosis via targeting T-box transcription factor 5 in inflamed synoviocytes. Issue 2 (13th April 2018) - Hussain, Nazim; Zhu, Wenhua; Jiang, Congshan; Xu, Jing; Geng, Manman; Wu, Xiaoying; Hussain, Safdar; Wang, Bo; Rajoka, Muhammad Shahid Riaz; Li, Yue; Tian, Juan; Meng, Liesu; et al.
Abstract : Synoviocytes from rheumatoid arthritis (RA) patients share certain features with tumor cells, such as over proliferation and invasion. Anomalous microRNA (miRNA) expression may participate in the pathogenesis of RA in different ways. The objective of the present study was to observe the role of miR-10a-5p targeting T-box transcription factor 5 (TBX5) gene on synoviocyte proliferation and apoptosis in RA. Human synovial sarcoma cell line, SW982 cells stimulating with interleukin-1β (IL-1β) were transfected with miR-10a-5p mimic and siRNA of TBX5. The real-time quantitative polymerase chain reaction (RT-qPCR) and Western blotting analysis were used to evaluate the expression level of miR-10a-5p and TBX5 in SW982 cells respectively. Further, the proliferation and apoptosis of SW982 cells after treatment were determined by cell counting kit (CCK-8) and flow cytometry analysis respectively. We found that the miR-10a-5p showed down-regulated while TBX5 showed up-regulated expression in synoviocytes after stimulation with IL-1β. The miR-10a-5p mimic treatment showed a decline in cell proliferation while the increased rate of cell apoptosis as compared with control. Moreover, knockdown of TBX5 favored the apoptosis and reduced the cell proliferation as compared with control group. We conclude that down-regulation of miR-10a-5p promotes proliferation and restricts apoptosis via targeting TBX5 in inflamed synoviocytes.